Vascular Leaking, a Pivotal and Early Pathogenetic Event in Systemic Sclerosis: Should the Door Be Closed? - Bruni, Cosimo; Frech, Tracy; Manetti, Mirko; Rossi, Francesca Wanda; Furst, Daniel E.; De Paulis, Amato; Rivellese, Felice; Guiducci, Serena; Matucci-Cerinic, Marco; Bellando-Randone, Silvia (Frontiers in Immunology, 2018)
The early phase of Systemic sclerosis (SSc) presents edema as one of the main features: this is clinically evident in the digital swelling (puffy fingers) as well as in the oedematous skin infiltration of the early active diffuse subset. Other organs could be affected by this same disease process, such as the lung (with the appearance of ground glass opacities) and the heart (with oedematous changes on cardiac magnetic resonance imaging). The genesis of tissue oedema is tightly linked to pathological changes in the endothelium: various reports demonstrated the effect of transforming growth factor β, vascular endothelial growth factor and hypoxia-reperfusion damage with reactive oxygen species generation in altering vascular permeability and extravasation, in particular in systemic sclerosis. This condition has an alteration in the glycocalyx thickness, reducing the protection of the vessel wall, causing non-fibrotic interstitial oedema, a marker of vascular leak. Moreover, changes in the junction adhesion molecule family and other adhesion molecules, such as ICAM and VCAM, are associated with an increased myeloid cells’ extravasation in the skin and increased myelofibroblasts transformation with further vascular leak and cellular migration. This mini-review examines current knowledge on determinants of vascular leak in SSc, shedding light on the role of vascular protection. This could enhance further studies in the light of drug development for early treatment, suggesting that the control of vascular leakage should be considered in the same way that vasodilation and inflammation reduction, as potential therapeutic targets.